(untitled) (Medico Legal Update, 2021)
Background: Methicillin-resistant Staphylococcus aureus (MRSA) is one of the most frequent causes of Nosocomial infections around the world. Aims: This study aimed to detect some diagnostic genes and some virulence factor genes for MRSA isolates. Method: During the period of from August to December 2019, 46 MRSA were isolated from different clinical samples such as Urinary Tract Infections (UTIs), Wounds infection’s, Diabetics foot patients, Burn patients and Otitis media in Al- Hussain Teaching Hospital in Thi-qar province, Iraq. All MRSA isolates were subjected to conventional Polymerase Chain Reaction to detect 16SrRNA and mecA genes and some virulence factors genes hla and tst-1 genes. Six PCR product were selected and subjected to partial DNA sequencing for the 16SrRNA gene to follow up their possible relationship between them and what recorded globally in Genbank. Results: The results revealed that all isolates 46(100%) have 16SrRNA, mecA, and hla genes, While only 23 isolated (50%) have tst-1 gene. The six PCR product of 16SrRNA was registered in Genbank under official accession numbers of (MT605393.1, MT605385.1, MT605394.1, MT605386.1, MT605387.1, and MT605388.1). The phylogenetic tree that was constructed by MEGA10 software showed that there were different molecular relationships among the local Staph. aureus isolates with analogous ones around the world.